Modern Clinical Diagnostic Methods for Menopausal Women Based on Vitamin D Levels - Nuriddinovna, Xudoynazarova Dilobar; Furkatovna, Amanova Madina (American Journal of Bioscience and Clinical Integrity, 2025)
In the evaluation of numerous population studies on the prevalence of vitamin D deficiency in different ethnic and age groups, a relationship between its deficiency and the duration and age of postmenopause has been found. The “gold standard” for the treatment of menopausal disorders is, of course, menopausal hormone therapy (MHT) in various forms. According to a number of authors, the addition of vitamin D metabolites to complex therapy can improve some metabolic parameters and clinical outcomes in elderly and postmenopausal women. However, there is insufficient information on how vitamin D metabolites interact with different types of MHT when used as part of combination therapy. Objective: To compare the severity of changes in serum vitamin D levels in women using different forms of HRT. Materials and methods: The study included 60 women aged 45-55 years in surgical postmenopause, which lasted from 1 to 5 years. Before the start of the study, all patients had vitamin D deficiency (less than 20 ng / ml). Depending on the type of HRT prescribed, the patients were divided into 2 groups of 30 people. In group 1, monotherapy with transdermal estrogens was prescribed (17β-estradiol - gel for external use). In group 2, combined estrogen-progestogen oral MHT (1 mg 17β-estradiol + 5 mg dydrogesterone) was prescribed. In addition to MHT, all patients received cholecalciferol (vitamin D) at a dose of 6000-8000 IU per day for 8 weeks. Research results: against the background of combined MHT, a significant increase in serum vitamin D levels was observed compared to the monotherapy group - with equal doses of drugs and the same initial level of vitamin deficiency. Conclusion: Screening for vitamin D deficiency is recommended for all patients before starting HRT. If vitamin D levels are low, combined estrogen-progestogen forms of HRT should be preferred.